2022
DOI: 10.1002/ece3.9352
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of Ellochelon vaigiensis (Quoy & Gaimard, 1825) living in the Mekong Delta, Vietnam

Abstract: Ellochelon vaigiensis (squaretail mullet) adapts to a wide salt spectrum, grows quickly and is easy to raise with other species, so it is the object of attention in aquaculture. Information on the biology and ecology of the species, diet, in particular, is still scattered. Here, we explore the feeding habit, feeding intensity, and food composition of the squaretail mullet. A total of 942 fish (526 males and 416 females) were collected from November 2020 to October 2021 at four coastal sites in the Mekong Delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Ashiq Ur Rahman et al [22] found that P. subviridis in the Parangipettai waters, India consumed detritus, diatoms, dinoflagellates, algae, zooplankton, polychaetes, foraminiferans, larval forms and miscellaneous items. Similar results were obtained for the other species of the mullet, Ellochelon vaigiensis in the Mekong Delta, Vietnam, where detritus was the essential food in the diet composition of the species and did not vary with sex, body size, season, and sampling site [48]. Several authors considered the diatoms were the most important food items for this species.…”
Section: Discussionsupporting
confidence: 81%
“…Ashiq Ur Rahman et al [22] found that P. subviridis in the Parangipettai waters, India consumed detritus, diatoms, dinoflagellates, algae, zooplankton, polychaetes, foraminiferans, larval forms and miscellaneous items. Similar results were obtained for the other species of the mullet, Ellochelon vaigiensis in the Mekong Delta, Vietnam, where detritus was the essential food in the diet composition of the species and did not vary with sex, body size, season, and sampling site [48]. Several authors considered the diatoms were the most important food items for this species.…”
Section: Discussionsupporting
confidence: 81%
“…The growth pattern of E. vaigiensis is negative allometry because the b value is <3 (2.13–2.68), and this fish is well adapted to the environment as the CF value approaches the well‐being threshold of 1 (0.97–1.13) (Dinh, Truong, Nguyen, Tran, et al., 2022 ). This squaretail mullet is an algi‐omnivorous with the food composition of mainly Bacillariophyta, followed by detritus (30.3%) and Cyanophyta (18.3%) (Dinh, Truong, Nguyen, Lam, et al., 2022 ). Nguyen et al.…”
Section: Introductionmentioning
confidence: 99%
“…This fish can reach the maximum length of 63 cm in Indo-Pacific and Caribbean regions [ 5 ], but common fish caught at 35 cm in the Western Central Pacific [ 6 ]. Ellochelon vaigiensis is available throughout the year and is considered to be an essential food source in the VMD [ 7 , 8 , 9 ], where it is facing the loss of habitats and population degradation due to anthropogenic and natural threats, e.g., overexploitation, environmental pollution, and climate change [ 10 ].…”
Section: Introductionmentioning
confidence: 99%